AZYGOS VEIN INJURY IN BLUNT CHEST TRAUMA - Drac, Pavel; Manak, Pavel; Klein, Jiri; Kral, Vladimir (Biomedical papers, 2007)
Injuries to the azygos vein in a blunt chest trauma are uncommon and have previously been described in only 21 cases. The diagnosis is crucially based on massive right haemothorax with signs of shock, hypotension and altered mental status. The severity of the trauma, speed of transport and surgical intervention are often decisive for the survival of the patient. This is confirmed by the three cases we report below.
Keywords: Azygos vein rupture/Blunt chest trauma/Massive haemothorax/Right thoracotomy